Changing course: Initiating the transformational learning process - Carolyn M. Clark (Adult Education Research Conference, 1993)
This study analyzed the initiating events of nine transformational learning experiences. Two types of initiators were found: the disorienting dilemma as described by Mezirow, and the integrating circumstance. How each functions to begin the transformational process is also discussed.